Simultaneous quantitation of lamivudine, zidovudine and nevirapine in human plasma by liquid chromatography-tandem mass spectrometry and application to a pharmacokinetic study - Murali Krishna Matta; Nageswara Rao Pilli; Jaswanth Kumar Inamadugu; Laxminarayana Burugula; Seshagiri Rao JVLN (Elsevier, 2012)
A rapid and sensitive LC-MS/MS method for the simultaneous quantitation of lamivudine, zidovudine and nevirapine in human plasma using abacavir as internal standard has been developed and validated. The analytes and IS were extracted from plasma by solid phase extraction using Oasis HLB cartridges and separated on a Hypurity Advance C18 column using a mixture of acetonitrile:0.1% formic acid (76:24, v/v) at a flow rate of 0.8 mL/min. Detection involved an API-4000 LC-MS/MS with electrospray ionization in the positive ion mode and multiple-reaction monitoring for analysis. The method was validated according to FDA guidelines and shown to provide intra- and inter-day precision and accuracy within acceptable limits in a run time of only 3.5 min. The method was successfully applied to a pharmacokinetic study involving a single oral administration of a combination tablet to human male volunteers.